Información, ¿antídoto frente al “populismo punitivo”?. Estudio sobre las actitudes hacia el castigo de los menores infractores y el sistema de Justicia Juvenil - Aizpurúa González, Eva (Revista Española de Investigación Criminológica, 2011)
The study of citizens’ attitudes towards the punishment of juvenile offenders has been established as one of the most prominent and prosperous spheres of research within Criminology. Its main findings have highlighted the ignorance of the general population towards the way in which the juvenile justice system is run. For this reason, the objective of this project is to analyze the effect of information in compensatory attitudes and perception of juvenile justice system, whilst observing the impact of socio-demographic, personal and instrumental variables. In order to achieve this, a quasi-experimental design has been implemented with a treatment group and a control group, in Talavera de la Reina. The collected results, consistent with the comparative research, show that public opinion is subject to the quantity and quality of the information at the community’s disposal. This verifies that as public awareness rises, punitive attitudes and unfavorable opinions against the juvenile justice system, fall. Likewise, the results reaffirm the complex and multifaceted nature of attitudes, influenced by multiple independent factors which are documented in international empirical research.